How Does Career Shock Moderate the Employee Career Establishment Process? - Evi Yulia; Budhi Haryanto; Ratna Handayati (AIBPM Publisher, 2022)
The purpose of this study is to predict the role of employee organization relationships in mediating the effects of competence development, empowering leadership on career success and role of career shock in moderating these relationships. Based on the results of the literature review, it is indicated that employee organization relationships mediate the positive influence of competence development, empowering leadership on career success. This means that the employee organization relationship is an effective stimulus to improve employee career formation. This study also indicates that These relationships will be stronger with increasing levels of positive career shock and weaker with increasing levels of negative career shock. The implication of this study is that career shock encourages employees to reflect critically on future career opportunities. Employees who invest in competence development and receive organizational support tend to have better long-term career prospects but career shock can increase or decrease their role in career success. Eventually, future research should be able to explore the concept of career shock and test it empirically because this concept is relatively new in career research.Keywords: competence development, empowering leadership, EOR, career shock, and career success